Disturbances in the ocular surface microbiome by perioperative antimicrobial eye drops - Hotta, Fumika; Eguchi, Hiroshi; Kuwahara, Tomomi; Nakayama-Imaohji, Haruyuki; Shimomura, Yoshikazu; Kusaka, Shunji (Frontiers in Cellular and Infection Microbiology, 2023)
We aimed to elucidate the effects of antimicrobial eye drops used in the perioperative period of ophthalmic surgery on the ocular surface microbiome by metagenomic analysis. Twenty-eight eyes from 15 patients (mean age 74.1 years) with no history of eye drop use within 3 months before cataract surgery were included in this study. Gatifloxacin eye drops were used in all patients in the perioperative period. The antimicrobial eye drops were started 3 days before surgery. They were discontinued after conjunctival sac specimen collection for 2 weeks after the surgery. Conjunctival sac specimens were collected to investigate the alterations in the ocular surface microbiome by meta-16S analysis targeting the V3-V4 region of the bacterial 16S rRNA gene. Principal coordinate analysis showed that the bacterial composition tended to be different before and 2 and 4 weeks after surgery. Individual observations on six eyes showed that the bacterial composition at 12 weeks after surgery was closer to that before surgery than to that at 4 weeks after surgery in two eyes, while the bacterial composition in the remaining four eyes was different at various time points. Before surgery, Firmicutes, Proteobacteria, and Bacteroidetes were predominant; however, 2 weeks after surgery, the proportion of Proteobacteria increased and that of Firmicutes decreased. A similar trend was noticed 4 weeks after surgery, although antibacterial eye drops had been discontinued 2 weeks after surgery. The Shannon–Weaver coefficient showed a decreasing trend at 2-, 4-, and 12-weeks post operation compared to that before operation. The diversity of the microbiome decreased significantly at 2- and 4-weeks after surgery when compared to that before surgery (p < 0.05). The ocular surface microbiome is easily disrupted by antimicrobial eye drops, and it needs recovery time. In such cases, the ocular surface microbiome is presumed to contain many antimicrobial-resistant bacteria. In some cases, it may not recover, and a new microbiome is formed.